A novel PPP2R2A:PRKD1 fusion in a cribriform adenocarcinoma of salivary gland. Issue 5 (3rd February 2023) - de Jager, Vincent D.; de Visscher, Sebastiaan A. H. J.; Schuuring, Ed; Doff, Jan J.; van Kempen, Léon C.
Abstract: Cribriform adenocarcinoma of salivary gland (CASG) is a rare, salivary gland tumor. In this report, we describe a case of CASG harboring a novel PPP2R2A::PRKD1 fusion. A 58‐year‐old female presented with an intraoral mass adjacent to the lower left third molar region. Morphological features at histological examination, immunohistochemical staining (p63+, p40−), and tumor location were indicative of CASG. However, due to the potential focal presence of a biphasic component within the tumor, RNA sequencing was performed to confirm the diagnosis. The subsequently found novel PPP2R2A::PRKD1 fusion adds to the rapidly evolving molecular landscape of salivary gland tumors. Additionally, we report that CASG may show some entrapment of pre‐existent salivary gland ducts, which may be misinterpreted as tumor cells with myoepithelial differentiation.